CLARITY - Tifanny Tanuwijaya; Budi Darma (Institute of Research and Community Outreach - Petra Christian University, 2017)
This creative project is a romantic suspense novel that tells about the emotional bond of a cruel psychopath, Lukas, who kidnaps people and commits drug exploitation on them, and Sharon, who is one of his victims. To develop the plot and the characterization, I used four theories: Psychoanalysis, Antisocial Personality Disorder, Stockholm syndrome and Dream Analysis. The themes are about perception, exploring that of the psychopath’s false perception about people’s lives, and purpose, in which we explore both the psychopath and the victim’s contradicting purpose. This novel will also explore the topics of drug exploitation, factors that trigger Stockholm syndrome to the victim, and the syndrome’s effects to both the psychopath and victim. These are to assist me in conveying my purpose of writing this novel which are to raise the ever-growing issue of kidnapping and drug abuse, so that people could raise their guard more; also, for the people to know the underlying causes of a problematic person’s actions, so they are not quick to judge.